Targeting a Novel RNA-Protein Interaction for Therapeutic Intervention of Hantavirus Disease - Salim, Nilshad N. (J Biol Chem, 2016)
An evolutionarily conserved sequence at the 5′ terminus of hantaviral genomic RNA plays an important role in viral transcription initiation and packaging of the viral genome into viral nucleocapsids. Interaction of viral nucleocapsid protein (N) with this conserved sequence facilitates mRNA translation by a unique N-mediated translation strategy. Whereas this evolutionarily conserved sequence facilitates virus replication with the assistance of N in eukaryotic hosts having multifaceted antiviral defense, we demonstrate its interaction with N presents a novel target for therapeutic intervention of hantavirus disease. Using a high throughput screening approach, we identified three lead inhibitors that bind and induce structural perturbations in N. The inhibitors interrupt N-RNA interaction and abrogate both viral genomic RNA synthesis and N-mediated translation strategy without affecting the canonical translation machinery of the host cell. The inhibitors are well tolerated by cells and inhibit hantavirus replication with the same potency as ribavarin, a commercially available antiviral. We report the identification of a unique chemical scaffold that disrupts a critical RNA-protein interaction in hantaviruses and holds promise for the development of the first anti-hantaviral therapeutic with broad spectrum antiviral activity.